2020
DOI: 10.3390/ijms21207678
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation and Myeloperoxidase-Related Oxidative Stress in the Pathogenesis of Genetically Triggered Thoracic Aortic Aneurysms

Abstract: Genetically triggered thoracic aortic aneurysms (TAAs) are usually considered to exhibit minimal levels of inflammation. However, emerging data demonstrate that specific features of an inflammatory response can be observed in TAA, and that the extent of the inflammatory response can be correlated with the severity, in both mouse models and in human studies. Myeloperoxidase (MPO) is a key mediator of the inflammatory response, via production of specific oxidative species, e.g., the hypohalous acids. Specific ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 152 publications
0
34
0
2
Order By: Relevance
“…MPO activity is an index of neutrophil infiltration and inflammation, and MPO can produce specific oxidative species ( Malecki et al, 2020 ). To evaluate the effect of the MPX-mediated anti-inflammatory response after E. coli infection, the levels of IL-2, IL-6, TNF-α, and MPO were detected by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…MPO activity is an index of neutrophil infiltration and inflammation, and MPO can produce specific oxidative species ( Malecki et al, 2020 ). To evaluate the effect of the MPX-mediated anti-inflammatory response after E. coli infection, the levels of IL-2, IL-6, TNF-α, and MPO were detected by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…This treatment might provide beneficial effects by preventing tissue damage and vascular dysfunction due to nitrosative stress caused by local pro-inflammatory conditions in the aortic wall of patients with MFS. 117 An earlier study also confirmed the efficacy of 1400W to improve the contractile function of thoracic aorta segments isolated from Fbn1 C1039G/+ mice, 104 lending further support to the rationale for testing iNOS inhibition for the treatment of MFS. Nevertheless, previous attempts to translate similar findings of protection afforded by (i)NOS inhibition in mouse models of sepsis, septic shock, and cardiogenic shock to the clinic have not been met with great success, 179 , 180 indicating that targeting NO production might not be an ideal strategy, and perhaps targeting upstream or downstream processes might be a more promising approach.…”
Section: Experimental Treatments Tested In Preclinical Studiesmentioning
confidence: 72%
“…Data from mouse models as well as from the clinic have shown that inflammation and oxidative stress play an important role in the pathophysiology of MFS. 117 A study by He et al on biopsies from patients with MFS undergoing elective aortic root repair demonstrated infiltration of immune cells into the aortic media and adventitia. 118 A significant influx of T cells and macrophages was found in the aortic segments.…”
Section: Pathophysiology Of Marfan Syndromementioning
confidence: 99%
“…Therefore, traditional herbal medicines have been searched as strong candidate materials with antioxidant activity for alleviating the inflammatory disorder [ 32 ]. Myeloperoxidase (MPO) is known as an important mediator of the inflammatory response through the production of specific oxidative species, e.g., the hypohalous acids (HOCL) [ 33 ]. Serum MPO markedly elevated 4.1 fold compared with the normal group, whereas UR treatment led to a significant reduction dose-dependently in rats.…”
Section: Discussionmentioning
confidence: 99%